The Alchemical/Chemical Image of Miners: A Preliminary Study - Stagni, Reno; Roxo Beltran, Maria Helena (Circumscribere International Journal for the History of Science, 2008)
A recurrent image in Renaissance alchemical imagery, miners digging for embryo-minerals appear in countless treatises as well as in compendia on the applications of “chemistry” into medicine, either as manuscripts or as printed books. However, this same image would be presented also in Renaissance treatises on mining and metallurgy, aiming to disclose the secrets of both arts. The present paper analyzes some of these images that circulated in Europe between the 15th and 17th centuries, aiming at pointing out to iconographic transformations related to the symbolism of miners‟ work.